2010
DOI: 10.1186/1471-2458-10-112
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low cure rate of tuberculosis in remote poor areas of Shaanxi Province, China: a case control study

Abstract: BackgroundThe directly observed therapy-short course (DOTS) strategy was introduced in Shaanxi province, China to improve tuberculosis (TB) control by means of improved case detection (target: > = 70%) and treatment success rates (target: > = 85%) in new smear positive (SS+) TB patients. At a provincial level the targets were both reached in 2005. However in 30 (28%) out of 107 counties of Shaanxi province the cure rate was below 85%. This study aimed to investigate patient and treatment characteristics associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 13 publications
6
42
0
1
Order By: Relevance
“…Karim et al in Bangladesh and Salami and Olubayo in Ilorin Nigeria reported that male were less likely to adhere to treatment leading to poorer outcomes [23,24]. Similarly, the study of WU et al in Taiwan and a case control study in China by Ai et al revealed that elderly patients and those above 60 years had poorer treatment outcomes respectively [25,26]. These findings were in contrast to our finding which showed that the sex and age of the patients were not significantly associated with the outcome of treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Karim et al in Bangladesh and Salami and Olubayo in Ilorin Nigeria reported that male were less likely to adhere to treatment leading to poorer outcomes [23,24]. Similarly, the study of WU et al in Taiwan and a case control study in China by Ai et al revealed that elderly patients and those above 60 years had poorer treatment outcomes respectively [25,26]. These findings were in contrast to our finding which showed that the sex and age of the patients were not significantly associated with the outcome of treatment.…”
Section: Discussionmentioning
confidence: 96%
“…The burden of TB in these finding accounts for defaulted treatment 5.1%, dead subjects 2.4%, failure 0.3%, and transfer-out 0.5% of all patients and among smear positive pulmonary TB there were defaulted treatment 5.4%, dead subjects 2.9%, failure 0.4%, and transfer-out 0.7% cases [11]. Similarly in different parts of the world defaulted treatment, death, failure and transferout cases are the real challenges for TB treatment [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…High age, male sex, low income, no or limited access to transport, distance from home to the treatment center, incomplete treatment compliance, limited interest in information about the disease and its treatment, limited social support, multidrug resistance, and Advances in Public Health 3 comorbidity have all been found to be related to unsuccessful treatment outcomes [13,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are several influential risk factors for treatment outcome of TB patients which have been identified so far. The following are among the recognized factors that lead to poor treatment outcome of the patients: male sex [7][8][9][10][11][12][13], old age [7,8,[14][15][16][17], unemployment [14,18], distance or travel cost to a healthcare facility [10,[18][19][20], being on retreatment [7,14,16,[21][22][23][24], TB/HIV co infection [9,10,22,[25][26][27], side effects of anti-TB drugs [10,[28][29][30][31], family size greater than 5 persons [14], having smearnegative pulmonary TB [7,8]. In addition, illiteracy [20,30,32], low educational level [27,31], substance abuse [10,…”
Section: Introductionmentioning
confidence: 99%